Features of providing broiler chickens with exchange energy and protein as important indicators of productivity and quality of the obtained products - L. M. Fijalovych; Ya.I. Kyryliv; G. А. Paskevych (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2019)
The article deals with the possibility of using feed additives in the feeding of broiler chickens and the peculiarities of their effect on the poultry organism. Contemporary data on the biological role of nutrients and energy in the feeding of broiler chickens are presented. The characteristics of the main feeds for poultry and the ways of reducing their prime cost in the conditions of broiler farms are given. The basic principles of effective feeding of poultry with forages of different content of metabolic energy and crude protein are considered, taking into account their assimilation in the body. Provided compound feed recipes and practical tips. It is established that high growth rate of broiler chickens in the start and groove periods (5–39 days) is provided by high-protein compound feeds – 23% (1–2 weeks), 21% (3–5 weeks) and exchange energy of 298 kcal and 305 kcal, respectively. With further cultivation in the finish forage the protein content in the forage decreases and the level of metabolic energy increases (up to 309 kcal). However, for each cross applies its own technology of cultivation and different rates of nutrients in raw materials. It is clear that effective breeding of broiler chickens is not possible without the proper rationing and use of protein and feed energy. Of course, provided that the supply of biologically active substances also corresponds to the normalized amount. Thus, the quality of poultry products is directly dependent on the quality of feed and the efficiency of transformation of feed energy into products.